Analisis kelimpahan plankton dan pertumbuhan kerang kepah Polymesoda erosa (Solander, 1786) yang dipelihara pada tambak di Delta Mahakam: Analysis of plankton abundance and growth of cultured mud clam in Mahakam Delta Pond - Samsul Rizal; Jailani (Fakultas Perikanan dan Ilmu Kelautan, Universitas Mulawarman, 2022)
This study was aimed to analyze the prospects of development of the This research was aimed to analyze the relationship between plankton abundance and morphometric growth of Mud Clam (Polymesoda erosa). The study was located in an idle brackish water pond in Mahakam Delta, by culturing Polymesoda erosa in small scale. Grouping random design was applied for sampling. Treatment was divided into factor A and B. Factor A is related to shell size: size I (40 – 60,99 mm), II (61 – 80,99 mm) and size III (81 – 100 mm). Factor B is indicating to study location with vegetation (Rhizophora sp) and no vegetation. In order to analyze plankton abundance, a quantitative descriptive analysis was applied, in addition of ANOVA test to analyze the growth. The result indicated that between two study ponds is different. The number of plankton per liter water from vegetated pond has more plankton individual than the sample from non-vegetated pond. The applied treatment on study ponds and shell size determined the morphometric growth and biometric. The growth of shell length is faster than that on height and thickness. The growth of mud clam in vegetated ponds relatively better that the pond without vegetation.